Behavior comparison of seven-types of steel–concrete composite stub columns under axial compression. (1st February 2022) - Zhang, Sumei; Li, Xiaozhong; Li, Jian; Lu, Wei; Chen, Jie
Highlights: Seven-type steel–concrete composite stub columns with the same steel ratio are tested under axial compression. The newly proposed steel-tube-confined concrete-filled steel tube is included. The influence of configurations on the mechanical properties of the composite column is determined and compared. The confinement mechanism of various steel–concrete composite columns is illustrated systematically. Current designing specifications are evaluated for different types of composite columns by the experimental results. Abstract: Steel-concrete composite columns are widely used in civil engineering structures for superior structural performance and economical cost. In response to the varying construction conditions, extensive types of composite columns have been developed nowadays, including concrete-filled steel tubes (CFST), CFST with steel bar (CFST-B) or steel section embedded (CFST-S), steel tubed concrete (T-C), steel tubed reinforced concrete (T-RC), steel tubed steel-reinforced concrete (T-SRC), and the newly proposed steel-tube-confined CFST (T-CFST), etc. A systematic and comparative experimental study was conducted for the seven types of steel–concrete composite stub columns with the same steel ratio, aiming to clarify their differences and facilitate an appropriate selection. Experimental results showed that all the conventional composite columns suffered from brittle failure, which was changed to ductile failure for T-CFST. Moreover, the employment of internal rebar or structural steel led to a variation of 13.3% in the ultimate load of CFST members; setting steel gap at the column ends for T-C columns increased the ultimate load by about 10% further; the addition of outer steel tube and sandwich material in T-CFST achieved up to 42.4% higher ultimate load. The enhanced mechanical properties of T-C and T-CFST were resulted from the increasing concrete confinement by the outer steel tube. The current design codes for different types of composite columns were examined by the experimental results, and a more suitable design method is needed for T-CFST.